Differentially expressed microRNAs in human depression: a systematic review of case-control and longitudinal studies - Yangyang He; Sanne Houtenbos; Pia-Maria Wippert (BMC Psychiatry)
Abstract Background Depression is a complex psychiatric condition characterized by a significant disturbance in an individual’s cognition, emotional regulation, and/or behavior. Previous studies have investigated potential cellular and molecular mechanisms for depression, including microRNA (miRNA), which are small, non-coding RNAs that affect several biological processes involved in the development of depression. This systematic review aims to synthesize current evidence on altered miRNA expression in depressed patients, thus in an effort to understand the intricate interactions between depression and miRNAs for upcoming diagnoses and therapies. Methods A systematic literature search was conducted in PubMed and Web of Science databases in November 2023. Studies were eligible if they (1) involved human depression studies, (2) investigated miRNA alterations, and (3) conducted case-control or longitudinal studies. After assessing the quality of studies with the NIH Quality Assessment Tool, the roles of altered miRNAs in depressed patients were synthesized. Results A total of 1452 studies were screened, and 37 studies were finally included (26 case-control and 11 longitudinal studies; n = 2909 patients), in which 48 different miRNA alterations among depressed patients were observed. The seven miRNAs that were most frequently studied and consistently exhibited altered expression across the included studies were miR-146a-5p, miR-132-3p, miR-124-3p, miR-16-5p, miR-155-5p, miR-135a-5p, and miR-451a, which mostly play a role in the release of molecules involved in neurobiological processes. Conclusions This systematic review illustrated the involvement of various miRNAs in the pathophysiology of depression, and identified miRNAs as potential diagnostic or therapeutic markers. These findings may contribute to the current understanding of miRNA-based biomarkers and new treatments for depression. Clinical trial number Not applicable.